Mycoplasma pneumoniae and Legionella pneu- mophila co-infection with SARS-CoV-2 infections in COVID-19 patients living in Abadan, Iran. (2021) - Soltani, Saber; Zandi, Milad; Fani, Mona; Elhami, Saeedeh; Zakeri, Armin; Pakzad, Reza; Abbasi, Samaneh
No abstract available